(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Despite advances in antibacterial therapy and imaging, benign acute cholangitis is still associated with high postoperative morbidity and mortality, largely related to forced single-stage radical operations performed in severely ill patients. Evidence is needed on whether a complex strategy prioritizing minimally invasive decompression, combined with pathogenetically based perioperative therapy, improves outcomes compared with the traditional approach.